THE HABIT OF READING STORY BOOKS IN IMPROVING EARLY CHILDHOOD LITERACY ABILITIES AT RAIHAN KARINA KINDERGARTEN MEDAN TEMBUNG - Dhea Amanda Siregar; Abdul Karim Batubara (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
A This study aims to describe the roles of teachers and parents in fostering storybook reading habits to enhance early childhood literacy at TK Raihan Karina, Medan Tembung. Using a qualitative case study approach, data were collected through observation, interviews, and documentation. The findings indicate that interactive reading activities at school and active parental involvement at home significantly influence children's reading interest, vocabulary acquisition, and comprehension. The success of literacy programs relies heavily on collaboration between school and home environments and the availability of age-appropriate and engaging reading materials.